2016
DOI: 10.1002/bdd.2015
|View full text |Cite
|
Sign up to set email alerts
|

The role of the equilibrative nucleoside transporter 1 on tissue and fetal distribution of ribavirin in the mouse

Abstract: Ribavirin is used for the treatment of hepatitis C virus (HCV) infection. The equilibrative nucleoside transporter 1 (ENT1) expressed in hepatocytes transports ribavirin into the liver, the site of efficacy of the drug. However, it is still unclear whether ENT1 plays a dominant role in the hepatic distribution of the drug in vivo. In addition, due to fetal toxicity, administration of ribavirin to pregnant women with HCV infection is contraindicated. ENT1 might play a role in the fetal distribution and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…13 ENT1 protein was found to be the predominant nucleoside transporter in placental MVMs (Table 1), as has already been confirmed at the functional and expressional levels. [8][9][10][11][12][13] The expression of ENT2 protein at human placental MVMs was under the limit of quantification according to our quantification analysis criteria, but this does not directly mean the absence of ENT2 protein. In fact, a positive peak was detected for 3 of 4 donors when only the most sensitive SRM transition for human ENT2 was considered, with a mean value of 0.74 fmol/mg protein (Supplemental Table S2).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…13 ENT1 protein was found to be the predominant nucleoside transporter in placental MVMs (Table 1), as has already been confirmed at the functional and expressional levels. [8][9][10][11][12][13] The expression of ENT2 protein at human placental MVMs was under the limit of quantification according to our quantification analysis criteria, but this does not directly mean the absence of ENT2 protein. In fact, a positive peak was detected for 3 of 4 donors when only the most sensitive SRM transition for human ENT2 was considered, with a mean value of 0.74 fmol/mg protein (Supplemental Table S2).…”
Section: Discussionsupporting
confidence: 68%
“…6,7 Among these transporters, ENT1, encoded by SLC29A1, is expressed at the microvillous membrane (MVM) of the syncytiotrophoblast layer in humans, mice, and rats 8-including ribavirin and abacavir. [12][13][14] The fetal distribution of ribavirin was significantly reduced in Ent1-knockout mice at 15 min after administration but no significant difference was seen at 2 h. 13 This may indicate that ENT1 affects the rate, but not the extent, of ribavirin distribution into the fetus, and thus may imply that other transporter proteins contribute to the fetal transfer of ribavirin. Candidate ribavirin transporters include human ENT1, ENT2 (encoded by SLC29A2), CNT2 (encoded by SLC28A2), and CNT3 (encoded by SLC28A3), which were shown to transport ribavirin when expressed in Xenopus oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…40 A knockout study in mice has shown that ent1 is responsible for hepatic uptake of ribavilin, which is used for the treatment of hepatitis C virus infection. 41 Iikura et al 42 have also reported that ENT1 is a possible determinant of the antiviral effectiveness of ribavirin by using OR6 cells as a hepatitis C virus replication system. It is thus likely that decreased expression of ent1 would lead to reduced pharmacological effects of these drugs during CA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 equilibrative nucleoside transporter (ENT1) is one kind of most abundant and widely distributed in plasma membrane nucleoside transporter in mammalian cells and tissues [ 15 , 16 ], and ENT1 is regarded as a critical transporter for the regulation of adenosine, and for the cellular uptake of chemotherapeutic nucleoside analogs [ 17 , 18 ]. Previous study has illustrated that ectogenic adenosine A1 agonists that are transported by ENT1 could be applied to target central nervous system (CNS) disorders because of its widely distributed in the brain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%